Exploring interpersonal dynamics - Perrewe, Pamela L.; Ganster, Daniel C. (Research in occupational stress and well being, 2004)
This is an annual research series devoted to the examination of occupational stress, health and well being, with particular emphasis on the multi-disciplinary nature of occupational stress. The intent is to pull together the various streams of research from a variety of disciplines to better capture the significant bodies of work in occupational stress and well being. We provide a multidisciplinary and international perspective that gives a thorough and critical assessment of issues in occupational stress and well being. The theme for this volume is: Exploring Interpersonal Dynamics. It covers - Workplace Aggression and Violence against Individuals and Organizations: Causes, Consequences, and Interventions; The Radiating Effects of Intimate Partner Violence on Occupational Stress and Well Being; The Changing Nature of Job Stress: Risk and Resources; Job Characteristics and Learning Behavior: Review and Psychological Mechanisms; Organizational Stress Through the Lens of Conservation of Resources (COR) Theory; The Role of 'Happiness' in Organizational Research: Past, Present and Future Directions; Display Rules and Strain in Service Jobs: What's Fairness Got to do With It? Stress and Well Being in the Context of Mentoring Processes: New Perspectives and Directions for Future Research.